2000
DOI: 10.1046/j.1570-7458.2000.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in location and acceptance of phloem sap combined with reduced concentration of phloem amino acids explain lowered performance of the aphid Rhopalosiphum padi on nitrogen deficient barley (Hordeum vulgare) seedlings

Abstract: Effects of nitrogen deficiency in hydroponically grown barley seedlings (Hordeum vulgare L.) on the development and reproduction of the aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) were investigated. Plant growth was significantly reduced in seedlings grown without nitrogen. Aphid intrinsic rate of increase (rm) was also significantly lower on these plants compared with that on plants grown with 8 mol m−3 nitrogen. Phloem sap was collected from seedling stems by aphid stylectomy and amino acids quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 21 publications
6
107
2
Order By: Relevance
“…Eleftherianos et al (2006) revealed an inverse correlation between the total concentration of plant total phenols in aphid-infested maize and barley plants. Similar relationships have also been observed for other aphid species, such as Metopolophium dirhodum Walker, 1849, Schizaphis graminum Rondani, 1852 and Diuraphis noxia Mordvilko, 1913(Havlickowa 1995, Ponder et al 2000Sandström et al 2000). Todd et al (1971) and Dreyer & Jones (1981) in in vitro experiments showed that phenolic compounds exerted a negative influence on growth and reproduction of such aphid species as S. graminum and M. persicae.…”
Section: Discussionsupporting
confidence: 72%
“…Eleftherianos et al (2006) revealed an inverse correlation between the total concentration of plant total phenols in aphid-infested maize and barley plants. Similar relationships have also been observed for other aphid species, such as Metopolophium dirhodum Walker, 1849, Schizaphis graminum Rondani, 1852 and Diuraphis noxia Mordvilko, 1913(Havlickowa 1995, Ponder et al 2000Sandström et al 2000). Todd et al (1971) and Dreyer & Jones (1981) in in vitro experiments showed that phenolic compounds exerted a negative influence on growth and reproduction of such aphid species as S. graminum and M. persicae.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the average ST sap total amino acid concentration was 460 mM, with a range of 134 to 1,047 mM. These values tend to be higher than previously published figures, which ranged from just below 200 mM to over 400 mM in alfalfa (Girousse et al, 1996) and were 180 mM in barley seedlings (Ponder et al, 2000), 69 mM in Dactylis glomerata (Hale et al, 2003), 262 mM in wheat, and 125 mM in rice Chino, 1986, 1990). However, high values of up to 1,232 mM have been reported in maize (Zea mays; Faria et al, 2007).…”
Section: Discussioncontrasting
confidence: 53%
“…Stylectomy was performed on feeding aphids using a high-frequency microcautery device (Unwin, 1978) as outlined by Ponder et al (2000) and Hale et al (2003). Stylectomy was always performed between 12 PM and 5.30 PM at 18°C to 20°C.…”
Section: St Sap Collection and Analysismentioning
confidence: 99%
“…Recent studies have used EPG assessments, and improved stylectomy techniques have enabled pure phloem sap to be obtained; several have demonstrated that nitrogen fertiliser applications increase phloem sap amino acid concentrations. Research with the cereal aphid Rhopalosiphum padi maintained in clip cages on hydroponically grown barley seedlings with 8 mM NH 4 NO 3 or without nitrogen [30], found that the N-deficient plants had significantly lower concentrations of non-essential amino acids and the aphids reared on them had a significantly lower intrinsic rate of increase. This situation was similar to the r m reported here, where there was a significant difference between the 0 rate and the 180 and 240 kg N/ha fertiliser rates in the glasshouse experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Techniques seeking to establish a closer link with sap components, plant nutrients and aphid performance have included the use of aphid stylectomy and electrical penetration graphs (EPG) to monitor aphid feeding. These studies, with different aphid species, have included the effects of aphid performance on hydroponically grown barley seedlings with no nutrient levels versus a high (8 mM) N solution [30], and on developmentally young potato plants with 'nutrient rich' phloem versus mature 'poor' phloem plants [29]; another study with aphids on milkweed used a narrow range of rates (0, 5 and 10 g N/m…”
mentioning
confidence: 99%